Pengaruh Customer Satisfaction, Adjusted Expectation, Perceived Value, dan Perceived Usefullness Terhadap Online Repurchase Intention pada Pelanggan Lazada - Laurensia Lagita; Vita Briliana (Jurnal Wira Ekonomi Mikroskil, 2018)
This study tries to investigate the impact of customer satisfaction, adjusted expectation, perceived value, and perceived usefulness towards customer online repurchase intention on www.lazada.co.id (case study: Jakarta). The data were collected using purposive sampling method and used 100 respondents. The research data is processed with IBM statistic 19 as a tool. The result of this research has shown that customer satisfaction, adjusted expectations, perceived value, and perceived usefulness, influence significantly towards online repurchase intention.